The Works and Times of Johan Huizinga (1872-1945) Writing History in the Age of Collapse - Rydin, Thor (Studies in the History of Knowledge, 2024)
The lifetime of Johan Huizinga (1872-1945) was marked by dramatic transformations in Europe. Cityscapes, aesthetic codes, social orders, political cultures, international travel and means of warfare developed beyond recognition; entire catalogues of hopes and fears were torn asunder and replaced by new ones during not one but two wars. Amidst all these changes, Huizinga grew to become one of the most famous historians of his time. To this day, his works are treated as monuments in the cultural historical field. This book examines how these transformations and 'experiences of loss' affected and informed Huizinga's historical perspectives. Most centrally, this book contends that Huizinga's historical works helped to accommodate and give meaning to his own experiences of uncertainty and rupture, thus offering him a way of life in turbulent times. This project offers an original and comprehensive analysis of an iconic historian writing in the age of collapse